Soft Tissue Microvascular Reconstruction of Orbital Exenteration Defects - Badhey, Arvind; Haidar, Yarah; Genden, Eric (Seminars in Plastic Surgery, 2019)
The main goal of head and neck reconstruction is the restoration of form and function. Oncologic surgery makes this process more complex, as the preplanned defect can be very different from its intraoperative counterpart. This emphasizes the role of preoperative planning and a diverse reconstructive “tool box” that can accommodate a variety of complicated defects. The other reconstructive goals are determined by the patient with the aid of an interdisciplinary team. While multiple local and regional reconstructive options are available, free tissue transfer provides a versatile and reliable option for reconstruction—especially for complex orbital defects. Here the authors discuss free soft tissue transfer options for orbital exenteration. This review will catalog the advantages and disadvantages of the radial forearm, rectus abdominis, latissimus, and anterolateral thigh.
Keywords: orbital reconstruction; orbital exenteration; free tissue transfer; head and neck reconstruction; soft tissue reconstruction